Studi Kajian Peluang Bisnis Pakan Kucing Di Era Digital - Rezki Apri Zulharji Siswanto; Rita Saragih; Yopi G.O.S Harefa; Friska Sitompul; Dewi Mahrani Rangkuty (Universitas 17 Agustus 1945 Semarang, 2023)
In today's digital era, cats are one of the most popular pets in the community. Cats are cute and adorable animals and can even be believed to relieve stress and reduce tension after doing daily activities. As the number of people who keep cats increases, of course, this has an impact on the sale of cat feed which is quite increasing where many people are in the cat feed business because it is a promising business. Types of cat feed consist of dry feed and wet feed that can be sold both online and offline.